Conformational changes and their role in non-radiative energy dissipation in photosystem II reaction centres - Litvín, Radek; Bína, David; Siffel, Pavel; Vácha, Frantisek (Photochemical & photobiological sciences, 2005)
Accumulation of reduced pheophytin in photosystem II under illumination at low redox potential is known to be accompanied by a pronounced decrease of a chlorophyll fluorescence yield. Simultaneous measurement of this fluorescence quenching and absorbance changes in photosystem II reaction centres, in the presence of dithionite, showed each event to have a different temperature dependence. While fluorescence quenching was suppressed more than 20 times when measured at 77 K, pheophytin accumulation decreased only 5 times. At 77 K, the fluorescence was quenched considerably, but only in those reaction centres where reduced pheophytin had been accumulated at room temperature before sample freezing. This showed that the accumulation of reduced pheophytin above 240 K was accompanied by an additional, most probably conformational, change in the reaction centre that substantially enhanced non-radiative dissipation of excitation energy.
Keywords: Photosystem II Protein Complex; světlo; Temperature; Chlorophyll; chlorofyl; kinetika; teplota; Spectrometry, Fluorescence; Light; fluorescenční spektrometrie; Kinetics; fotosystém II (proteinový komplex)